A study on the marketing communication mix by Kopetro Travel and Tours Kerteh / Mahyudi Kaban - Kaban, Mahyudi (1999)
Kopetro Travel & Tours-located in Kerteh were established in 1992 owned by Koperasi Kakitangan Petronas Bhd. It was registered with Ministry of Arts, Cultural, and Tourism Malaysia and a member of Matta (Malaysia Association of Travel and Tours agency). In 1994, this company joined the International Air Transport Association (IATA) which allowing it to issue air tickets independently. KTTK operations are in 470 square foot area organized around air travel with more than 20 different travel related services. Prospective travelers and tourists can fulfill their needs in various nature and destination. KTTK offering air tickets, hotel reservation, car rental and team building trips also incentives, training programs, holiday packages, individual and group packages to the world, expeditions, youth travel, safaris, sport and adventure travel. Specialized expert team’s help to consult clients in various aspects so that highest level of services can be provided. Sophisticated infrastructure help KTTK to provides efficient and fast services resulting savings and wider services range that can be taken into account. The business is backed by financial stability, service standard and travels industry professional knowledge. The company thus proven to offer more value for money, best and wider services ranges. Apart from that it is the most dynamically developing among travel agency within this region. The scope of the study focused on the marketing communication mix currently practiced in the agency for its various services. There’s lots of services offered but still the demand is not achieving the level where it can fully utilized its resources of manpower